Staphylococcus aureus alpha-toxin inhibits CD8+ T cell-mediated killing of cancer cells in cutaneous T-cell lymphoma. (1st January 2020) - Blümel, Edda; Munir Ahmad, Shamaila; Nastasi, Claudia; Willerslev-Olsen, Andreas; Gluud, Maria; Fredholm, Simon; Hu, Tengpeng; Surewaard, Bas G. J.; Lindahl, Lise M.; Fogh, Hanne; Koralov, Sergei B.; Rahbek Gjerdrum, Lise Mette; et al.
ABSTRACT: Staphylococcus aureus and its toxins have been linked to disease progression and mortality in advanced stages of cutaneous T-cell lymphoma (CTCL). CD8 + T cells play a crucial role in anti-cancer responses and high CD8 + T cell numbers in tumor lesions are associated with a favorable prognosis in CTCL. Here, we show that CD8 + T cells from both healthy donors and Sézary syndrome patients are highly susceptible to cell death induced by Staphylococcal alpha-toxin, whereas malignant T cells are not. Importantly, alpha-toxin almost completely blocks cytotoxic killing of CTCL tumor cells by peptide-specific CD8 + T cells, leading to their escape from induced cell death and continued proliferation. These findings suggest that alpha-toxin may favor the persistence of malignant CTCL cells in vivo by inhibiting CD8 + T cell cytotoxicity. Thus, we propose a novel mechanism by which colonization with Staphylococcus aureus may contribute to cancer immune evasion and disease progression in CTCL.